Malaysian researchers on open data: The first national survey on awareness, practices and attitudes - Hodonu-Wusu, James Oluwaseyi; Noorhidawati, A.; Abrizah, A. (Malaysian Journal of Library and Information Science, 2020)
The study investigates the awareness, practices and attitudes of researchers in regard to open data – i.e. the sharing and reuse of research data – which is part of a larger study that concentrated on the scholarly communication readiness of Malaysian researchers in Open Science. The data were gathered by means of a survey which obtained 135 responses from researchers based in five research universities in Malaysia. The main conclusions are: (a) the researchers are aware of open data, yet, they are not practising it as shown in the mean scores, as well as in their responses towards the statements asked; (b) unclear information on data privacy policy, misuse of data, and the fear of losing publication opportunity are part of disincentives for data sharing. The requisite for open data understanding, practices and attitudinal change is needed for these may impact research practices, government policies and scientific knowledge, leading to research transparency and accountability, social benefit and economic growth. This paper concludes with a discussion that policies incentivizing the sharing and reuse of open data, as well as tools and guidance to support data sharing, and a strong incentives and rewards to implement open data among researchers, should be encouraged. Future studies should look into the importance of rewards for data sharing among researchers’ institutions. Studies bridging the gap between policy and practices of open data should be examined, if true openness in research is to be established in Malaysia.